Osteoblast Hypoxia-Inducible Factor-1α Pathway Activation Restrains Osteoclastogenesis via the Interleukin-33-MicroRNA-34a-Notch1 Pathway - Kang, Hui; Yang, Kai; Xiao, Lianbo; Guo, Lei; Guo, Changjun; Yan, Yufei; Qi, Jin; Wang, Fei; Ryffel, Bernhard; Li, Changwei; Deng, Lianfu (Frontiers in Immunology, 2017)
Functional cross-talk between osteoblasts and osteoclasts is a key process for bone homeostasis. Although osteoblast hypoxia inducible factor-1α (HIF-1α) pathway activation results in impaired osteoclastogenesis via the direct regulation of osteoprotegerin (OPG), it is unclear whether there are other efficient mediators are involved in osteoblast HIF-1α pathway activation-restrained osteoclast formation. In addition to upregulated OPG, we observed that osteoblast HIF-1α activation led to increased interleukin-33 (IL-33) expression, which was found to inhibit osteoclastogenesis. Mechanistically, HIF-1α facilitates IL-33 expression by binding to -1504/-1500 bp on the Il-33 promoter. IL-33, thereby, acts on bone marrow-derived monocytes (BMMs) to reduce their osteoclastic differentiation. Moreover, microRNA-34a-5p (miR-34a-5p)-inhibited Notch1 activation was observed to play a central role in this process. Thereby, the identification of IL-33-miR-34a-5p-Notch1 pathway in the inhibitory effect of osteoblast HIF-1α pathway on osteoclastogenesis uncovers a new mechanism for understanding the effects of HIF-1α on bone remodeling.